2019
DOI: 10.1055/s-0039-1688789
|View full text |Cite
|
Sign up to set email alerts
|

Cangrelor versus Ticagrelor in Patients Treated with Primary Percutaneous Coronary Intervention: Impact on Platelet Activity, Myocardial Microvascular Function and Infarct Size: A Randomized Controlled Trial

Abstract: Background Oral P2Y12 inhibitors take more than 2 hours to achieve full effect in healthy subjects and this action is further delayed in patients with acute myocardial infarction. Intravenous P2Y12 inhibition might lead to more timely and potent anti-platelet effect in the context of emergency primary angioplasty, improving myocardial recovery. Objectives This article compares the efficacy of intravenous cangrelor versus ticagrelor in a ST-elevation myocardial infarction (STEMI) population treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“… 32 Alexopoulos et al 34 reported that HRPR was 6.7% at 15 minutes and 0% at 1 hour (using VerifyNow and a cutoff of PRU >208) in 15 patients with STEMI receiving cangrelor (pretreated with ticagrelor; none of them received morphine). Ubaid et al 35 reported an HRPR rate of 10% (using VerifyNow and a cutoff of PRU >208) at the time of balloon inflation in 50 cangrelor-treated patients with STEMI. In Buchtele et al, 36 16 cardiac arrest survivors with STEMI, who were treated with targeted temperature management, received cangrelor, and none had HRPR (using Multiplate Analyzer, platelet function had a median 18 U, interquartile range 10 to 25; <46 U was used as the cutoff).…”
Section: Discussionmentioning
confidence: 99%
“… 32 Alexopoulos et al 34 reported that HRPR was 6.7% at 15 minutes and 0% at 1 hour (using VerifyNow and a cutoff of PRU >208) in 15 patients with STEMI receiving cangrelor (pretreated with ticagrelor; none of them received morphine). Ubaid et al 35 reported an HRPR rate of 10% (using VerifyNow and a cutoff of PRU >208) at the time of balloon inflation in 50 cangrelor-treated patients with STEMI. In Buchtele et al, 36 16 cardiac arrest survivors with STEMI, who were treated with targeted temperature management, received cangrelor, and none had HRPR (using Multiplate Analyzer, platelet function had a median 18 U, interquartile range 10 to 25; <46 U was used as the cutoff).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of difference in ST resolution between the two strategies suggests a lack of differential effect on impairment of the microvascular circulation. Other work has shown that potent P2Y 12 inhibition at the time of PPCI with cangrelor did not translate into improvement in infarct size or microvascular circulation [24]. As such, it appears that antithrombotic treatment is needed as a preventative therapy rather than as an intervention to aid microvascular circulation.…”
Section: Discussionmentioning
confidence: 98%
“…As such, it appears that antithrombotic treatment is needed as a preventative therapy rather than as an intervention to aid microvascular circulation. Although cangrelor may be an attractive option to circumvent the delayed absorption of ticagrelor or prasugrel, it has only been studied as a 2-4 hour infusion, which may not be sufficient to cover the delayed onset of action of oral P2Y 12 inhibitors in all patients [14,24]. Furthermore, it may not be affordable in many healthcare settings to offer cangrelor as a routine 6-hour infusion to opiate-treated STEMI patients undergoing PPCI.…”
Section: Discussionmentioning
confidence: 99%
“…35 It has been recently reported that cangrelor produces potent PRU-based P2Y12 inhibition even at the time of PPCI, although coronary microvascular function and infarct size are not improved. 36 Moreover, crushed P2Y12 inhibitor tablets may be effective in reducing plateletderived thrombogenicity during PPCI. The administration of crushed prasugrel or ticagrelor resulted in faster platelet inhibition compared with ingestion of the whole tablet in the setting of STEMI.…”
Section: Discussionmentioning
confidence: 99%